DIFFERENCES IN MICROHARDNESS OF MICROHYBRID COMPOSITE RESIN AFTER EXPOSURE TO ALCOHOL-BASED, ALCOHOL-FREE, AND HERBAL MOUTHWASHES: AN IN VITRO STUDY - Reni Purba, Member; Erawati, Suci; Surta Simbolon, Winda (Journal of Health and Dental Sciences, 2026)
Composite resin is one of the most widely used restorative materials in dentistry due to its aesthetic properties, mechanical strength, and ease of manipulation. However, the long-term mechanical stability of composite resins can be affected by chemical exposure, such as from mouthwash solutions used in daily oral hygiene routines. This study aimed to determine the difference in microhardness of microhybrid composite resin after immersion in mouthwash containing alcohol, alcohol-free mouthwash, and herbal mouthwash. This was an experimental laboratory study with a pre-test and post-test group design. A total of 30 samples of microhybrid composite resin (Solare X) were divided into three groups, each immersed for 48 hours at 36°C in Listerine Multi Protect Zero (alcohol-containing), MeToo Mouthwash Probiotic (alcohol-free), and Amodent Gargle with Cardamom Essential Oil (herbal). The microhardness values were measured using a Vickers Hardness Tester, and the data were analyzed using One Way ANOVA followed by Post Hoc Bonferroni tests. The results showed a significant increase in surface hardness after immersion in all groups, with the highest mean value in the alcohol-containing mouthwash group (32.85 VHN), followed by the herbal mouthwash (29.23 VHN), and the alcohol-free mouthwash (24.05 VHN) (p < 0.05). It can be concluded that all types of mouthwash have a significant effect on the surface hardness of microhybrid composite resin. The increase in hardness is likely due to the high filler content, strong silane coupling, and post-cure polymerization process occurring during immersion DOI : 10.54052/jhds.v5n3.p321-330